Pengembangan media digital scrapbook untuk meningkatkan pemahaman konsep matematika siswa kelas 4 pada materi pengukuranPENGEMBANGAN MEDIA DIGITAL SCRAPBOOK UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS 4 PADA MATERI PENGUKURAN - Juwita Juwita; Donna Boedi Maritasari; Iwan Usma Wardani (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to develop a digital scrapbook media to deliver measurement material and support the learning process at SDN 1 Ketangga for the 2024/2025 academic year. This research falls under the category of research and development (RD) utilizing the ADDIE development model, which consists of five steps: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research was conducted with fourth-grade students, totaling 14 students. The instruments used in this study include validation sheets, pretest-posttest assessments, and student response questionnaires. The results of the validation test by media experts showed a score of 74, which falls within the range of 61.2 X ≤ 75.6, categorized as "good." Meanwhile, the validation results from subject matter experts recorded a score of 79, which is within the range of X 70.8, placing it in the "very good" category. The results from the student response questionnaire regarding the validity and effectiveness of the developed media, comparing "yes" and "no" responses, indicated a "very good" response with a percentage of "yes" answers reaching 93% overall. Thus, it can be concluded that the digital scrapbook media is appropriate, valid, and effective for use in schools.